ChemInform Abstract: Broad Scope Hydrofunctionalization of Styrene Derivatives Using Iron‐Catalyzed Hydromagnesiation. Issue 17 (April 2015) - Jones, Alison S.; Paliga, James F.; Greenhalgh, Mark D.; Quibell, Jacob M.; Steven, Alan; Thomas, Stephen P.
Abstract An operationally simple, chemo‐ and regioselective hydromagnesiation reaction generates benzylic Grignard reagents.